Effects of Mannan Oligosaccharide (MOS) and Xylo Oligosaccharide (XOS) Supplementation on the Growth Performance of Broilers - Vasudevan, G.; Vijayarani, K.; Karunakaran, R.; Srithar, A.; Meignanalakshmi, S.; Raja, P.; Ramesh, J.; Varun, A. (International Journal of Livestock Research, 2019)
Antibiotics have been widely used in the field of poultry production as growth promoters for the last five decades. However, this practice has resulted in the development of antibiotic resistance in birds and human. Prebiotics can be used as an alternative to antibiotics to enhance the growth rate and upregulate the immune response of the host. In the present study, 108 numbers of day old broiler chicks were randomly divided in to 9 groups of 12 birds with 6 replicates in each group. The group T1 was kept as control. Birds in the other treatment groups were fed with different dietary concentrations of prebiotics - either mannan oligosaccharide (MOS) or xylo oligosaccharide (XOS) (T2– 0.2% MOS, T3 – 0.5% MOS, T4 – 0.75% MOS, T5 – 1% MOS, T6 - 0.2% XOS, T7 – 0.5% XOS, T8 – 0.75% XOS and T9 – 1% XOS) for a period of 42 days. The body weight was recorded at weekly intervals up to 42 days of age. Birds fed with 0.75% MOS (T4), 1% MOS (T5), 0.5% XOS (T7), 0.75% XOS (T8) and 1% XOS (T9) in their diet recorded significantly (P<0.05) higher body weight and feed conversion efficiency, when compared to the control and other treatment groups. There is no significant difference among the treatment groups T1 (control), T2 (0.2% MOS), T3 (0.5% MOS) and T6 (0.2% XOS) in the parameters studied. This study revealed that an optimum concentration of 0.75% of MOS and 0.5% of XOS can safely be included in the diet of broilers with beneficial effects on growth performance and immunomodulation.